Oxidative stress and heart rate variability in patients with vertigo. Issue 3 (11th December 2014) - Ohara, Keiichiro; Inoue, Yoshiaki; Sumi, Yuka; Morikawa, Miki; Matsuda, Shigeru; Okamoto, Ken; Tanaka, Hiroshi
Abstract : Aims: Peripheral vertigo has been reported to result from oxidative stress or autonomic nervous dysfunction. Recently, heart rate variability has been used to evaluate autonomic nervous activity. Parasympathetic nervous dysfunction is associated with peripheral vertigo; however, the relationships between vertigo, oxidative stress, and autonomic nervous activity have not been investigated. The aim of this study was to elucidate the changes in oxidative stress and autonomic nervous activity in vertigo patients compared with healthy volunteers. Methods: Oxidative stress was assessed by evaluating biological antioxidant potential and reactive oxygen metabolites, and heart rate variability was measured to evaluate autonomic nervous activity. Thirty‐four patients who complained of peripheral vertigo and were treated in our emergency department between January and August 2011 were enrolled in study 1. Oxidative stress and heart rate variability were measured and compared with those of healthy volunteers ( n  = 23). In study 2, oxidative stress in 18 vertigo patients and heart rate variability in 41 vertigo patients were measured between January and August 2012 before and after conventional treatment of vertigo to evaluate the effect of the treatment on oxidative stress and autonomic nervous activity. Results: Reactive oxygen metabolites were higher in vertigo patients than in healthy volunteers. Parasympathetic nervous activity was lower and the sympathetic/parasympathetic nervous activity ratio (autonomic nervous activity ratio) was higher in vertigo patients than in healthy volunteers. After treatment of vertigo, reactive oxygen metabolites decreased significantly and the autonomic nervous activity ratio became similar to that observed in healthy volunteers. Conclusions: Bedside monitoring of oxidative stress and heart rate variability may be useful for the diagnosis of vertigo and evaluation of the effect of treatment.